Quantitative text analysis and the study of EU lobbying and interest groups. (September 2015) - Bunea, Adriana; Ibenskas, Raimondas
Interest groups' policy position documents constitute an important data source for estimating their policy positions and lobbying success. We examine applications of quantitative text analysis to research these documents in the context of the European Commission's open consultations. We show a considerable degree of incongruity between this method's assumptions and the text characteristics of EU position documents. We examine how these incongruities affect the validity of position estimates and conduct an empirical analysis of documents submitted in one consultation on CO2 car emissions. We compare estimates derived on both quantitative and qualitative content analysis and find relatively limited correspondence between the two. These observed differences matter substantively: they result in different findings concerning levels of interest groups' lobbying success.